Stat3 activation in human endometrial and cervical cancers - Chun‐Liang Chen; F-C Hsieh; Jacqueline Lieblein; Jessica A. Brown; Carina K. Y. Chan; James A. Wallace; Gong Cheng; Brett M. Hall; Jiayuh Lin (2007)
The activation of signal transducer and activator of transcription 3 (Stat3) has been implicated in the oncogenesis of cancer and is regarded as a novel target for cancer therapy. Stat3 is classified as a proto-oncogene, because an activated form of Stat3 can mediate oncogenic transformation in cultured cells and tumour formation in nude mice. The constitutive activation of Stat3 has been frequently detected in various types of human cancers. However, the constitutive activation of Stat3 in endometrial and cervical cancers has not been studied. We examined tyrosine phosphorylation of Stat3 (activated form of Stat3) in multiple endometrial and cervical cancer tissues using tissue microarray slides as well as cancer cell lines to explore the possible activation of Stat3. Our results indicated that elevated phosphorylation of Stat3 was detected in cervical and endometrial cancer cell lines. Our results also showed that elevated levels of phosphorylation of Stat3 protein were detected in the endometrial and cervical cancer specimens. This is the first study to demonstrate that Stat3 is activated in human endometrial and cervical cancer tissues. Immunohistochemical staining showed that activated Stat3 is associated with increased expression of downstream antiapoptotic genes, Bcl-xL, survivin, and Mcl-1 in these tissues. Expression of a dominant-negative Stat3 mutant using adenovirus-mediated gene transfer inhibited cell growth and induced apoptosis in HeLa and SiHa cervical cancer cell lines expressing elevated levels of Stat3 phosphorylation. Further, a JAK/Stat3 small molecular inhibitor, JSI-124, induced apoptosis more selectively in HeLa and SiHa cancer cell lines than Ishikawa cell line without elevated levels of Stat3 phosphorylation. These results indicate that Stat3 is activated in human endometrial and cervical cancers and the inhibition of constitutive Stat3 signaling may be an effective target for cancer intervention in these two cancers.